212k views
1 vote
Hello need it asap I will give you 5 star for all answer

Hello need it asap I will give you 5 star for all answer-example-1
Hello need it asap I will give you 5 star for all answer-example-1
Hello need it asap I will give you 5 star for all answer-example-2
Hello need it asap I will give you 5 star for all answer-example-3
Hello need it asap I will give you 5 star for all answer-example-4

1 Answer

2 votes

Answer:x f(x) = 2.5x − 10.5 g(x) = 64(0.5x)

2 f(2) = 2.5(2) - 10.5 g(2) = 64(0.5*2)

f(2) = 5 - 10.5 g(2) = 64(1)

f(2) = -5.5 g(2) = 64

3 f(3) = 2.5(3) - 10.5 g(3) = 64(0.5*3)

f(3) = 7.5 - 10.5 g(3) = 64(1.5)

f(3) = -3 g(3) = 96

4 f(4) = 2.5(4) - 10.5 g(4) = 64(0.5*4)

f(4) = 10 - 10.5 g(4) = 64(2)

f(4) = -0.5 g(4) = 128

5 f(5) = 2.5(5) - 10.5 g(5) = 64(0.5*5)

f(5) = 12.5 - 10.5 g(5) = 64(2.5)

f(5) = 2 g(5) = 160

6 f(6) = 2.5(6) - 10.5 g(6) = 64(0.5*6)

f(6) = 15 - 10.5 g(6) = 64(3)

f(6) = 4.5 g(6) = 192

User Nomura Nori
by
6.6k points